FAKTOR RISIKO GANGGUAN MUSKULOSKELETAL PADA MAHASISWA KESEHATAN MASYARAKAT UPN VETERAN JAKARTA TAHUN 2022 - Septiana Renata, (2022)
Musculoskeletal Disorders are complaints of the musculoskeletal system that can occured in students with non-ergonomic body postures when used laptops while studying because of static activities for a long time. This study aims to determine the risk factors of musculoskeletal disorders in Public Health students at UPN Veteran Jakarta. The research method used quantitative analysis with a cross-sectional study design. The research population is active students of Public Health UPN Veteran Jakarta with a total sample of 223 students. The research instrument used a body posture questionnaire and the Nordic Body Map. The proportion of students who experience MSDs complaints is 37.2%. Based on the results of bivariate analysis with the chi square test, it showed that there was a relation between age (POR 2.19; 95%CI (1.23-3.91), sitting duration (POR 0.23; 95%CI (0.12-0.44) and body posture (POR 0.20; 95% CI (0.11-0.36) for MSDs complaints. Meanwhile, there was no relation between gender, body mass index, and exercise habits with MSDs complaints in college students. Based on the results of the study, it is recommended that during learning activities, students have to do a good sitting posture and stretch the body every 20 minutes to avoid muscle tension. Students are expected to be able to manage good time management on the duration of sitting in order to reduce the risk of pain in the musculoskeletal system due to poor sitting position because of long sitting duration.